Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/jnr.21777
|View full text |Cite
|
Sign up to set email alerts
|

17β‐Estradiol attenuates hyperoxia‐induced apoptosis in mouse C8‐D1A cell line

Abstract: In premature infants, oxygen free radicals generated following neonatal resuscitation are associated with subsequent diseases such as retinopathy of prematurity and bronchopulmonary dysplasia. Recent studies in brain tissue samples have shown that nonphysiologic oxygen levels play a key role in induction of apoptosis in the developing brain. Estrogen is a well-established agent in neuroprotection and, therefore, is thought to be neuroprotective even in the premature brain. Astrocytes appear to have a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…cular diseases, such as hypertension and atherosclerosis, by dilating blood vessels and increasing blood flow (28). E 2 may increase the activity of endothelial cells, inhibit endothelial cell apoptosis, promote endothelial cell proliferation, facilitate angiogenesis and the growth of blood vessels and play an important role in retinal vascular development (29,30,33).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…cular diseases, such as hypertension and atherosclerosis, by dilating blood vessels and increasing blood flow (28). E 2 may increase the activity of endothelial cells, inhibit endothelial cell apoptosis, promote endothelial cell proliferation, facilitate angiogenesis and the growth of blood vessels and play an important role in retinal vascular development (29,30,33).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that ER-mediated E 2 plays an important role in normal retinal vascular development and ROP pathogenesis (35). Maternal E 2 levels during pregnancy may increase by ~100-fold (33,(35)(36)(37)(38)(39). Fetal E 2 levels increase with gestational age, with the E 2 concentration peaking between 33 and 36 weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations